Unexpected kinetically controlled organoselenium-based isomaleimide: X-ray structure, hirshfeld surface analysis, 3D energy framework approach, and density functional theory calculation - Shaaban, Saad; Ferjani, Hela; Abd El-Lateef, Hany M.; Khalaf, Mai M.; Gouda, Mohamed; Alaasar, Mohamed; Yousef, Tarek A. (Frontiers in Chemistry, 2022)
The unexpected isomaleimide 5-((4-((4-bromophenyl)selanyl)phenyl)imino)furan-2(5H)-one (4) was obtained in 77% yield instead of the maleimide 5 via dehydration and ring closure of the corresponding 4-((4-((4-bromobenzyl)selanyl)phenyl)amino)-4-oxobut-2-enoic acid (3) upon heating with acetic anhy-dride. The molecular structure of compound 4 was confirmed by mass spectrometry, 1H- and 13C-NMR spectroscopy, and X-ray diffraction analysis. Their cytotoxicity was assessed against two oligodendrocytes, and their respective redox properties were evaluated using 2′,7′-dichlorodihydrofluorescein diacetate (H2-DCFDA) assay. Furthermore, their antiapoptotic potential was also evaluated by flow cytometry. The compound crystallizes in triclinic P-1 space group with unit cell parameters a = 5.7880(4) Å, b = 9.8913(6)Å, c = 14.5951(9) Å, V = 1731.0 (3) Å3 and Z = 2. The crystal packing is stabilized by hydrogen bonding, π···π, C-Br···π stacking interactions, and other intermolecular interactions. The mapping of dif-ferent Hirshfeld surfaces and 2D-fingerprint were used to investigate intermolecular interactions. The interaction energies that stabilize the crystal packing were calculated and graphically represented as framework energy diagrams. We present a computational investigation of compound 4's molecular structure at the DFT level using the B3LYP method and the 6-31G ++ basis set in this paper. The optimized structure matches the experimental outcome. The global reactivity descriptors and molecular electrostatic potential (M.E.P.) map emphasize the molecule's reactive locations, allowing reactivity prediction. The charge transfer properties of molecules can be estimated by examining frontier molecular orbitals.